The role of upfront primary tumor resection in asymptomatic patients with unresectable stage IV colorectal cancer: A systematic review and meta-analysis - Liang, Zongyu; Liu, Zhiyuan; Huang, Chengzhi; Chen, Xin; Zhang, Zhaojun; Xiang, Meijuan; Hu, Weixian; Wang, Junjiang; Feng, Xingyu; Yao, Xueqing (Frontiers in Surgery, 2023)
Background: Controversy exists over the role of upfront primary tumor resection (PTR) in asymptomatic patients with unresectable stage IV colorectal cancer (CRC). The purpose of this study was to evaluate the effect of upfront PTR on survival outcomes and adverse outcomes. Methods: Searches were conducted on PubMed, EMBASE, Web of Science, and Cochrane Library from inception to August 2021. Studies comparing survival outcomes with or without adverse outcomes between PTR and non-PTR treatments were included. Review Manager 5.3 was applied for meta-analyses with a random-effects model whenever possible. Results: Overall, 20 studies with 3088 patients were finally included in this systematic review. Compared with non-PTR, upfront PTR was associated with better 3-year (HR: 0.69, 95% CI: 0.57-0.83, P = 0.0001) and 5-year overall survival (OS) (HR: 0.77, 95% CI: 0.62-0.95, P = 0.01), while subgroup analysis indicated that there was no significant difference between upfront PTR and upfront chemotherapy (CT) group. In addition, grade 3 or higher adverse effects due to CT were more frequent in the PTR group with marginal significance (OR: 1.74, 95% CI: 0.99-3.06, P = 0.05), and other adverse outcomes were comparable. Conclusions: PTR might be related to improved OS for asymptomatic patients with unresectable stage IV CRC, whereas receiving upfront CT is a rational alternative without detrimental influence on survival or adverse outcomes compared with upfront PTR.